Responses of Daphnia (Daphnia magna) to Titanium Dioxide Nanoparticles and Cilantro (Coriandrum sativum) - Francisco, Jose; Cha, Jihyung; Calonia, Sheila Marie P.; Hre, Solomon Van; Evangelista, Ephraim; Arce, Leilani D.; Pedro, Merbeth Christine L.; Tubilag, Edgar E.; Yllano, Orlex B. (8ISC Abstract Proceedings, 2022)
Nanotechnology is a revolutionary technology with immense applications in medicine, the manufacturing industry, electronics, energy, and the environment. The ubiquitousness and increased use of nanoparticles pose a health hazard, toxicity, and environmental concern. This study analyzed the responses of Daphnia to titanium dioxide (TiO2) nanoparticles and Cilantro. ANOVA results showed a very significant decrease in the heart rate of Daphnia after exposure (120 min) to various concentrations of TiO2 and Cilantro. Duncan's Multiple Range Test revealed a significant increase and decrease in the heart rate of Daphnia in different concentrations of TiO2 and Cilantro after the initial and final time of exposure, respectively. Mortality of Daphnia in different concentrations was not statistically different with the control and the treated setups (1 ppm, 3 ppm, and 5 ppm). This study is vital in understanding the responses of a test organism (Daphnia) to TiO2 nanoparticles. Keywords : nanoparticles, titanium dioxide, metals, Daphnia magna, Coriandrum sativum